Site‐Selective Alkenylation of Unactivated C(sp3)−H Bonds Mediated by Compact Sulfate Radical - Ueda, Mitsuhiro; Kamikawa, Kazuya; Fukuyama, Takahide; Wang, Yi‐Ting; Wu, Yen‐Ku; Ryu, Ilhyong (Angewandte Chemie International Edition, 2021)
A broad variety of unactivated acyclic and alicyclic substrates cleanly undergo site‐selective alkenylation of unactivated C(sp3)−H bonds with 1,2‐bis(phenylsulfonyl)ethene in the presence of persulfate. This simple transformation furnishes (E)‐2‐alkylvinylphenylsulfones in up to 88 % yield. In contrast with the previously reported decatungstate protocol, the current method is applicable to alkenylation of sterically hindered C−H bonds. This important advantage significantly broadens the substrate scope, and is attributed to the compact size of the sulfate radical employed in the C−H activation and cleavage. Reported here is a new protocol using persulfate anion for site‐selective C(sp3)−H alkenylation with 1,2‐bis(phenylsulfonyl)ethene. As shown, the alkenylation of (3aR)‐(+)‐sclareolide occurs site‐selectively at C8 in spite of the presence of 18 types of C(sp3)−H bonds in the molecule. The hydrogen‐atom transfer reaction by the sulfate radical follows radical polar effects, akin to the decatungstate anion but with a more controlled steric effect.